Pengembangan Media Etno-POE (Etnosains-Predict, Observe, Explain) Berbasis Android Pada Pokok Bahasan Getaran, Gelombang, dan Bunyi - Ningtyas, Triana Oktavia; Jumini, Sri; Firdaus, Firdaus (Universitas PGRI Semarang, 2022)
Android-Based Ethno-POE Media on the subject of vibration, waves, and sound is a development product that is relevant in the era of technological development as it is today, namely in the form of android-based learning media. In addition, the developed media contains elements of ethnoscience in the form of traditional Wonosobo musical instruments known as Bundengan. The addition of ethnoscience elements in the media is one of the real manifestations in the effort to preserve local culture. The type of research is research and development. The procedure used in this study uses the 4D development procedure that has 4 stages of development, namely define, design, develop, and disseminate. Data collection techniques using the method of questionnaires. Then, the data sources were obtained from primary data and secondary data (books and articles related to ethnoscience, POE, android, and vibration, waves, and sound materials) with junior high school students as research subjects. Data analysis using product validity. The result show that: (1) Android-based Ethno-POE media is declared feasible after going through validation by three validators with an average score percentage of 85% and is in the